Danish Research Libraries – Danish Models - Thorhauge, Jens (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In Europe we tend to think of cultural diversity as the very essence of our European fabric. This conference has also underlined the necessity for sticking to internationally recognised standards if we want a seamless cooperation in the future. So I believe that presenting the Danish situation to you serves a dual purpose: that of confirming that basically we do the things you do, but we also do some things in a different way which hopefully might be inspiring. I shall be looking at both aspects, with the main emphasis on the Danish models.